Chronic periodontitis and risk of lung cancer: a nationwide cohort study - Kim, Bo-Guen; Lee, Hyun; Lee, Sun-Kyung; Paik, Sun Young; Yun, Seo-Hyoung; Park, Chang-Joo; Yeo, Yoomi; Park, Tai Sun; Moon, Ji-Yong; Kim, Tae-Hyung; Sohn, Jang Won; Kim, Sang-Heon; et al. (Frontiers in Oncology, 2024)
Background The impact of long-term chronic periodontal conditions on the risk of lung cancer could not be accurately evaluated. Our aim was to provide more evidence on the connection between chronic periodontitis (CP) and lung cancer using a nationwide dataset. Methods This study used data from the Korean National Health Insurance Service National Sample Cohort. We enrolled 72,658 individuals with CP (CP cohort) between 2005 and 2019 and 1:1 age- and sex-matched controls without CP (non-CP cohort). Results During the median follow-up period of 5.1 (interquartile range, 2.8–8.0) years, 0.56% (n = 405/72,658) of the CP cohort and 0.29% (n = 212/72,658) of the matched non-CP cohort developed lung cancer, with incidence rates of 8.3 and 4.5 per 10,000 person-years. The risk of incident lung cancer was significantly higher in the CP cohort than in the matched non-CP cohort (adjusted hazard ratio = 2.27, 95% confidence interval = 1.94–2.65). The risk of incident lung cancer was 2.45-fold and 2.10-fold higher in mild and moderate-to-severe CP cohorts than in the matched non-CP control. The risk of incident lung cancer was especially higher in the 40–59 age group, females, and never-smokers than their counterparts. Conclusion We demonstrate that the risk of incident lung cancer is higher in individuals with CP than in those without. The risk of lung cancer was especially high in individuals with more severe CP, females, never-smokers, and obese populations.